Transformation of functional family and reconstruction of home in Jhumpa Lahiri’s the Lowland - Pour, Sharareh Rafiei (2017)
Jhumpa Lahiri, an American writer with South Asian origin, has continued writing about immigrant families and their attempt to construct home in her latest novel The Lowland shortlisted for 2013 Man Booker Prize. Lahiri can be uniquely categorized among the immigrant writers dealing with “imaginary homeland.” In this dissertation, I specifically focus on how Lahiri extends the concept of “home” by showing her main character trying to create his “imaginary homeland” in America, while his beloved brother in India is fighting to reconstruct their homeland by joining Naxalite Movement ended up being executed, while the parents are forced to witness the scene. The concept of “Home” used in this dissertation is discussed through the theories of Rosemary Marangoly George, which is here connected to “Social Imaginary” or “imagination as social practice” defined by Arjun Appadurai, connoting that our world shifts as we move from one place to another. The idea of “ethnoscape” defined by Appadurai will be discussed in this research in order to show how Lahiri depicts the stability and flow of these characters’ life affected by immigration. Moreover, the notion of family and family structure transformation for immigrants is under scrutinization in this research work exploring the ways in which Lahiri attempts to depict immigration changing the structures of the families, which is resulted from the global movement of people.